House of Care (HoC) Sebagai Metode Konseling Teman Sebaya Dalam Pencegahan dan Penangan Kekerasan Siswa di SMP Muhammadiyah 2 Yogyakarta - Harianto, Eko; Kusumastuti, Wanodya (Yayasan Rahmat Islamiyah, 2025)
This community service initiative aims to raise awareness about the importance of peer counselling. It is expected to help adolescents solve their problems, particularly within school environments and surrounding communities. The program was conducted through training sessions to prepare students to become peer counsellors. Additionally, SMP Muhammadiyah 2 Yogyakarta, through its Guidance and Counseling (BK) teachers, has developed a method called the House of Care (HoC) as a peer counselling approach. The outcomes of this program include increased knowledge and understanding among students regarding adolescent issues and the formation of peer counsellors. The activity was attended by 80 students from all grade levels who registered voluntarily to participate in the HoC program. The results showed high enthusiasm from participants and a significant improvement in their knowledge and skills related to the material, successfully forming 80 peer counsellors. Through this program, it is hoped that peer counsellors can serve as a viable solution to address various student challenges within and outside the school environment.